2013
DOI: 10.1063/1.4818761
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nnp and npp Auger recombination as significant contributor to the efficiency droop in (GaIn)N quantum wells by visualization of hot carriers in photoluminescence

Abstract: We report the direct observation of hot carriers generated by Auger recombination via photoluminescence spectroscopy on tailored (AlGaIn)N multiple quantum well (QW) structures containing alternating green and ultra-violet (UV) emitting (GaIn)N QWs. Optically pumping solely the green QWs using a blue emitting high power laser diode, carrier densities similar to electrical light-emitting diode (LED) operation were achieved, circumventing possible leakage and injection effects. This way, luminescence from the UV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 23 publications
1
94
1
Order By: Relevance
“…However, their determination becomes possible, if the measured DLT of non-equilibrium carriers is additionally involved. Starting from the rate equation for the unsteady carrier density 4) and considering δn(t) to be a small perturbation of the steady-state carrier density n, one can show that the perturbation decays mono-exponentially with the DLT τ = (A + 2Bn + 3Cn 2 ) −1 . In terms of the normalized optical power p the DLT can be expressed by…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, their determination becomes possible, if the measured DLT of non-equilibrium carriers is additionally involved. Starting from the rate equation for the unsteady carrier density 4) and considering δn(t) to be a small perturbation of the steady-state carrier density n, one can show that the perturbation decays mono-exponentially with the DLT τ = (A + 2Bn + 3Cn 2 ) −1 . In terms of the normalized optical power p the DLT can be expressed by…”
Section: Theorymentioning
confidence: 99%
“…the reduction of efficiency with increasing drive current, 1,2) which has been discussed widely in literature and has been attributed to Auger recombination [3][4][5] experimentally. In addition, an extension of the emission wavelength into the "Green Gap" 1,6) has proven to be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[5] For example, recent measurements have shown that III-N LEDs exhibit notable hot carrier distributions already close to the peak efficiency, [6][7][8][9] suggesting that hot carriers might have a more profound effect on the device characteristics than previously anticipated.…”
Section: Doi: 101002/aelm201600494mentioning
confidence: 98%
“…This suggests that the details of the band structure do not lead to crucial qualitative differences in describing the hot electron signature of Auger electron emission. This may also imply that the hydrodynamic (HD) model, also based on evaluating the moments of the BTE [8] like DD, could be able to provide and alternative and relatively fast approach that would, unlike DD, be able to account for the overflow currents at high biases while being computationally lighter than MC. However, as we have not yet made any practical comparisons of the HD model with our present results, it is too early to speculate if it can indeed provide any practical improvements over DD.…”
Section: Comparison Of Band Structure Modelsmentioning
confidence: 99%
See 1 more Smart Citation